(untitled) (Research, Society and Development, 2022)
Objective: To examine and map the scientific evidence on patient safety in the vaccine room according to the view of the nursing team. Method: Scoping Review, based on the procedures recommended by the Joanna Briggs Institute. The study adopted the following guiding question: “What is the understanding of the nursing team regarding safe care in vaccine rooms in Brazil?”. Searches were carried out in four databases, resulting in a final sample of seven studies analyzed. Results: The largest number of publications (n ​​= 4) was in 2019, followed by (n = 3) in 2021. Most studies come from the Southeast region, followed by two studies carried out in the Northeast region. Vaccine room professionals find barriers to safe care for the vaccinated person, dividing them into four categories: structural and environmental factors; Organizational factors of the service and work process; Professional and formative factors and Patient factors. The studies also show potential strategies for the safe care of the vaccinated. Conclusion: As resources to enhance patient safety, this study points to the importance of maintaining permanent educational processes in services, using information systems and conducting new research in the area of ​​patient safety in immunization. Continuing education initiatives need to be able to awaken professionals to change their attitude through reflection on their work process.